Respuesta :

  • 6x - 2y + z = -2 .......... (i)
  • 2x + 3y – 3z = 11 ...........(ii)
  • х + 6у = 31 ..............(iii)

After Multiplying 3 with the eq. (i) we will add this to eq. (ii)

[tex] \sf 18x - 6y + 3z = - 2[/tex]

[tex] \sf2x + 3y - 3z = 11[/tex]

_______________________

[tex]⇒ \sf20x - 3y = 9 \: \: .........(iv)[/tex]

After Multiplying 2 with the eq. (iv) we will add this to eq. (iii)

[tex] \sf \: x + 6y = 31[/tex]

[tex] \sf40x - 6y = 18[/tex]

_________________

[tex] \sf \: 41x = 49[/tex]

[tex]⇒ \sf \: x = \frac{49}{41} [/tex]

After putting the value of x in the eq. (iii)

[tex] \sf \frac{49}{41} + 6y = 31[/tex]

[tex]⇒ \sf6y = 31 - \frac{49}{41} [/tex]

[tex] \sf \: ⇒ 6y = \frac{1271 - 49 }{41} [/tex]

[tex]⇒ \sf6y = \frac{1222}{41} [/tex]

[tex]⇒ \sf \: y = \frac{1222}{41 \times 6} [/tex]

[tex]⇒ \sf \: y = \frac{611}{123} [/tex]

After putting the value of x and y into eq. (i)

[tex] \sf6 \times \frac{49}{41} - 2 \times \frac{611}{123} + z = -2 [/tex]

[tex]⇒ \sf\frac{294}{41} - \frac{1222}{123} + 2 = - z[/tex]

[tex]⇒ \sf \frac{882 - 1222 + 246}{123} = - z[/tex]

[tex]⇒ \sf - \frac{94}{123} = - z[/tex]

[tex]⇒ \sf \: z = \frac{94}{123} [/tex]

Hence,

[tex] \bf • \: The \: value \: of \: x = \frac{49}{41}

[tex] \bf • \: The \: value \: of \: x = \frac{49}{41} [/tex]

[tex] \bf • \: The \: value \: of \: y = \frac{611}{123}

[tex] \bf • \: The \: value \: of \: y = \frac{611}{123}[/tex]

[tex] \bf• \: The \: value \: of \: z \: = \frac{94}{123}[/tex]